If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -7 = 8 + 6x + 12 Reorder the terms: -7 + -3x = 8 + 6x + 12 Reorder the terms: -7 + -3x = 8 + 12 + 6x Combine like terms: 8 + 12 = 20 -7 + -3x = 20 + 6x Solving -7 + -3x = 20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + -3x + -6x = 20 + 6x + -6x Combine like terms: -3x + -6x = -9x -7 + -9x = 20 + 6x + -6x Combine like terms: 6x + -6x = 0 -7 + -9x = 20 + 0 -7 + -9x = 20 Add '7' to each side of the equation. -7 + 7 + -9x = 20 + 7 Combine like terms: -7 + 7 = 0 0 + -9x = 20 + 7 -9x = 20 + 7 Combine like terms: 20 + 7 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| -4/5*(11/3) | | 1+9b=-2b+10b+10 | | 77=x+5+7x | | -5/6*4/7 | | 2l^2-6l-108=0 | | -y+12-12y=3 | | 2/3*(0.8) | | -1/2(2x-4)-2x=5 | | 2/3*0.8 | | 3y-5+4y-9= | | (25a^2b^6)^1/2 | | (10x^3-21x^2-55x-18)/(5x+2) | | -32=-12+4x | | 3y-5+5+5y-9= | | -(x+-10)=7 | | (4*2)-y=3y | | -(x+10)=7 | | (-1/4-(-4))/-1/4-(1/8) | | 4y-2(y-3)+4= | | 2(x-3)-3(x+5)=3(x-2)-7 | | 2x=4360 | | 2x=(4360) | | 5(a+3)=3*1-a*a | | -9=5m+1 | | 5p-8p=14 | | x-(x*10/100)=2160 | | 10g^2-490=0 | | 15/8x31/3x2 | | -3x+2+7x=-2 | | -2x-2x=27-3 | | -13=-h+-7 | | 27-11x=10x-33 |